A problem-orientable numerical algorithm for modeling multi-dimensional radiative MHD flows in astrophysics: the hierarchical solution scenario - Hujeirat, Ahmad (Numerical methods in multidimensional radiative transfer, 2009)
We present a hierarchical algorithm for the adaptation of numerical solvers in high energy astrophysics. This approach is based on clustering the entries of the global Jacobian in a hierarchical manner that enables employing a variety of solution procedures ranging from a purely explicit time-stepping up to fully implicit schemes. A gradual coupling of the radiative MHD equation with the radiative transfer equation in higher dimensions is possible. Using this approach, it is possible to follow the evolution of strongly time-dependent flows with low/high accuracies and with efficiency comparable to explicit methods, as well as searching quasi-stationary solutions for highly viscous flows. In particular, it is shown that the hierarchical approach is capable of modeling the formation of jets in active galactic nuclei and reproduce the corresponding spectral energy distribution with a reasonable accuracy.
Gesehen am 26.06.2018